2014
DOI: 10.3233/bme-141188
|View full text |Cite
|
Sign up to set email alerts
|

Effects of innovative virtual reality game and EMG biofeedback on neuromotor control in cerebral palsy

Abstract: Sensorimotor control dysfunction or dyskinesia is a hallmark of neuromuscular impairment in children with cerebral palsy (CP), and is often implicated in reaching and grasping deficiencies due to a neuromuscular imbalance between the triceps and biceps. To mitigate such muscle imbalances, an innovative electromyography (EMG)-virtual reality (VR) biofeedback system were designed to provide accurate information about muscle activation and motivation. However, the clinical efficacy of this approach has not yet be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…6 This approach combines engagement and motivation to succeed at the game while working on specific active range of motion (AROM) with the overall aim of improving function. 7,8 This technology has been reported in the literature for MACS levels I to IV as a means of engaging children with CP in activities targeting bimanual control, 9 functional strength, and motor ability. 6,10 The literature has shown that participants in virtual reality-, web-, and computer-based interventions have the potential for improving muscle activation and functional muscle strength as well as increasing overall physical engagement.…”
Section: Bimanual Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…6 This approach combines engagement and motivation to succeed at the game while working on specific active range of motion (AROM) with the overall aim of improving function. 7,8 This technology has been reported in the literature for MACS levels I to IV as a means of engaging children with CP in activities targeting bimanual control, 9 functional strength, and motor ability. 6,10 The literature has shown that participants in virtual reality-, web-, and computer-based interventions have the potential for improving muscle activation and functional muscle strength as well as increasing overall physical engagement.…”
Section: Bimanual Trainingmentioning
confidence: 99%
“…6,10 The literature has shown that participants in virtual reality-, web-, and computer-based interventions have the potential for improving muscle activation and functional muscle strength as well as increasing overall physical engagement. [6][7][8] However, overall evidence is insufficient; more robust randomized controlled trials are needed to determine the effectiveness of these interventions.…”
Section: Bimanual Trainingmentioning
confidence: 99%
“…By using a VR headset, one can see the patient body and their parts digitally in different angles. [10][11][12] This technology increases the confidence of the patient by decreasing their fear when they are using VR glasses as it provides information closer to the real-life situation. By using this technology, a heart surgeon can now check the heart rate of the patient and its changes in rate.…”
Section: Introductionmentioning
confidence: 99%
“…Physical rehabilitation focusses on motor abilities and sensorimotor functioning. Serious games have been developed to aid in the rehabilitation of balance impairments ( Betker et al, 2006 ), motor functions of the hand ( Afyouni et al, 2017 ) and the upper limbs ( Broeren et al, 2008 ; Yoo et al, 2014 ), for instance. Motor rehabilitation games take a restitution-based rehabilitation approach, in which the aim is to restore impaired functions through intense and repeated stimulation of that function ( Wolf et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%